Training on Digital Module Creation and Implementation in the Independent Curriculum: Pelatihan Pembuatan Modul Digital dan Implementasinya Dalam Kurikulum Merdeka - Putri Dewi Nurhasana; Susanti Faipri Selegi; Ema Agustina; Murjainah; Dian Maharani Putri; Meliana Siregar (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Dedication to the community is focused on mentoring and training to improve the skills of teachers in SDN 22 Talang Kelapa in developing digital teaching modules and implementing in the independent curriculum. This mentoring and training is motivated by teachers' difficulties in developing teaching modules that suit students' needs and implementing them in the independent curriculum. In the independent curriculum, the module is an important component in implementing classroom learning. Through PKM activities it is hoped that partners will improve their skills in producing modules that suit the learning needs of students. Thus, the creation of a conducive learning environment also influences student achievement. Therefore, this PKM aims to produce modules that suit the needs of students so that the modules become valid, practical, and effective teaching materials to use; create modules by utilizing applications/programs that are easy to use; implement digital modules according to the needs of students in class; To what extent is the effectiveness of digital modules used in classroom learning into the independent curriculum. The method used to achieve PKM goals is through lecture methods, mentoring, and training. Materials related to training are delivered using the lecture method, then the creation of modules and the implementation of the modules are carried out directly in practice and with mentoring. This PKM activity as a whole got good and satisfying results.